Protein-Restricted Diets for Ameliorating Motor Fluctuations in Parkinson's Disease - Wang, Luxi; Xiong, Nian; Huang, Jinsha; Guo, Shiyi; Liu, Ling; Han, Chao; Zhang, Guoxin; Jiang, Haiyang; Ma, Kai; Xia, Yun; Xu, Xiaoyun; Li, Jie; et al. (Frontiers in Aging Neuroscience, 2017)
Levodopa is considered to be the most effective symptomatic drug for Parkinson’s disease (PD). As the disease progresses, however, the patients are likely to experience a reduced response to levodopa and develop motor fluctuations (i.e., end-of-dose wearing off and unpredictable “on-off”). Protein-rich diets and elevated plasma concentrations of large neutral amino acids have been proved to impair the therapeutic effect of levodopa by reducing its absorption and influx into the brain. On the other hand, the protein-restricted diets including low-protein diet (LPD), protein-redistribution diet (PRD) and PRD with use of low-protein products can all improve the efficacy of levodopa in patients with motor fluctuations. However, it should be noted that protein-restricted diets may also contribute to several side effects, including dyskinesia, weight loss and malnutrition (e.g. protein and calcium insufficiency). Together, protein-restricted diets are an effective approach to improve motor fluctuations in PD patients, while long-term adherence to these diets requires monitoring for side effects.